Hyperglycemic emergencies in athletes - Chansky, M. E.; Corbett, J. G.; Cohen, E. (Clinics in Sports Medicine, 2009)
Diabetes Mellitus is a chronic disorder affecting many adolescents and young adults participating in athletic activity at various levels. If blood glucose levels are managed incorrectly during periods of exercise, diabetes mellitus can lead to various endocrine emergencies, including hypoglycemia, hyperglycemia, and most seriously diabetic ketoacidosis. This article will review the epidemiology of diabetes mellitus, the body's response to exercise in a non-diabetic versus a diabetic, and the pathophysiology, clinical features, treatment, and prevention of hyperglycemic emergencies in athletes.